No sex-specific effects of balance training on dynamic balance performance in healthy children - Muehlbauer, Thomas; Schedler, Simon (Frontiers in Sports and Active Living, 2022)
Background Cross-sectional studies in children reported better balance performance for girls than for boys. Thus, balance trainability might be different between female and male children. The aim of the present study was to examine the effects of balance training (BT) on dynamic balance performance in girls compared to boys. Methods Seventeen girls (age: 11.1 ± 0.7 years) and 22 boys (age: 11.1 ± 0.8 years) were assigned to either a BT-group or an active control (CON) group. BT was conducted over eight weeks (two sessions/week) while the CON-groups received their regular physical education lessons during the same period. Before and after treatment, dynamic balance performance was assessed by using the Lower Quarter Y-Balance (YBT-LQ) test. A series of three-way analyses of covariance (ANCOVA) were undertaken to test for within-between effects of Test [×2 (pretest vs. posttest)], Group [×2 (BT-group vs. CON-group)] and Sex [×2 (boys vs. girls)]. Results The three-way ANCOVA yielded a significant main effect of Test (p = 0.002–0.043, ηp2 = 0.122–0.262) and of Group (all p < 0.001, ηp2 = 0.330–0.651) but not of sex for all YBT-LQ reach directions and the composite score. Further, there were significant Test × Group interactions (all p < 0.001, ηp2 = 0.330–0.651) in favor of both BT-groups but neither Test × Sex nor Test × Group × Sex interactions were detected. Conclusions We conclude that BT is an effective treatment to improve dynamic balance performance in healthy children regardless of their sex. Consequently, girls and boys can be provided with the same BT regime to enhance their postural control.